Determinants of economic literacy at university level: A case of Pakistan - Farrah Yasmin; Rehana Kouser; Ibn e Hassan; Waqar Ahmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The main intention of this study is to identify the determinants of economic literacy at university level. The data used in this study was collected by researchers through field survey by randomly selecting 200 students from different departments of the universities located in the Southern part of the Punjab province in Pakistan. Ordinary least square (OLS) technique and Logit model were used for empirical analysis. It is found that spending, age, gender, father's education and student's education were positive and significantly related to economic literacy. While the variables; mother's education and bank account were statistically significant but negatively related to the respondents' level of economic literacy. However, ATM used record, internet connection; resident's location and guardian's occupation were statistically insignificant with economic literacy. The study contributes towards the current understanding of the state of economic literacy among the young students. It also suggests the factors, which have significantly contributed towards the current economic literacy in Pakistani students.
Keywords: 330; economic literacy; ordinary least square; logit model; Pakistan